Giraffes [videorecording (DVD)] : Africa's gentle giants - Christie, Paul (Paul Anthony); Fennessy, Julian; Fennessy, Julian (Nature., 2016)
Conservationist Julian Fennessy, in collaboration with the Ugandan Wildlife Authority, embarks on a mission to transport twenty endangered giraffes to safety.